Molecular Mechanism of Tumor Cell Immune Escape Mediated by CD24/Siglec-10 - Yin, Shan-Shan; Gao, Feng-Hou (Frontiers in Immunology, 2020)
Tumor immune escape is an important part of tumorigenesis and development. Tumor cells can develop a variety of immunosuppressive mechanisms to combat tumor immunity. Exploring tumor cells that escape immune surveillance through the molecular mechanism of related immunosuppression in-depth is helpful to develop the treatment strategies of targeted tumor immune escape. The latest studies show that CD24 on the surface of tumor cells interacts with Siglec-10 on the surface of immune cells to promote the immune escape of tumor cells. It is necessary to comment on the molecular mechanism of inhibiting the activation of immune cells through the interaction between CD24 on tumor cells and Siglec-10 on immune cells, and a treatment strategy of tumors through targeting CD24 on the surface of tumor cells or Siglec-10 on immune cells.